Using Fuzzy Approach to Model Skill Shortage in Vietnam’s Labor Market in the Context of Industry 4.0 - Duong, M. T. H.; Nguyen, D. V.; Nguyen, P. T. (Engineering, Technology & Applied Science Research, 2020)
Human resource development is one of the main issues in the socio-economic development strategy and the transform of any regions in the context of the Industry 4.0. However, Vietnamese human resources have been poorly evaluated in the areas of quality, lack of dynamism, and creativity. Therefore, this paper presents fuzzy logic approach to ranking seven skills shortage in Vietnam’s Labor Market, namely lifelong learning, adaptive capacity, information technology capacity, creativity and innovation capacity, problem-solving capacity, foreign language competency, and organizing and managing competency. The result results shown that the problem solving skill is the largest gap between an enterprise’s requirements and the actual response of employees.